Empowering couples of childbearing age to become active family planning acceptors to create quality families - Uliarta Marbun; Irnawati; Hasnita (LPPM Politeknik Sandi Karsa, 2025)
The Family Planning (KB) Program is one of the government's strategies in controlling the population growth rate and realising quality families. Couples of childbearing age (PUS) are the main target in this program, but many PUS still have not yet become active family planning acceptors, especially in rural and remote areas. This community service activity aims to increase the understanding and participation of PUS in the use of contraceptives through education and counseling. The implementation method involved lectures, discussions, demonstration of contraceptives, and using leaflet media and teaching aids to 20 participants in the work area of the Pattingalloang Health Center, Makassar. The activity results showed an increase in the enthusiasm and knowledge of participants regarding the importance of being an active family planning acceptor. Supporting factors for the activity's success include the support of health workers, cadres, and the availability of infrastructure, while time constraints and the number of participants are obstacles. It is hoped that this activity can strengthen the role of PUS in the success of the family planning program and create healthy, prosperous, and quality families